Questioning your doubts : a Harvard PhD explores challenges to faith - Powell, Christina M. H., 1967- (Downers Grove : InterVarsity Press, 2014)
How can we know if God is real? Why did God allow my friend to become a rape victim? Is this person the one I should marry? Sometimes we have intellectual questions about the plausibility of God. Other times we go through difficult life experiences that cause us to question our faith. Sometimes we simply struggle feeling confident with day-to-day decisions. Powell struggled with the mysterious claims of a God who exists beyond what the scientific method could detect. Using personal stories from her own life, she explores how faith can be rooted in rationality, knowledge and facts, while coming to recognize the limits of science in evaluating matters of faith.
Thinking through doubts -- Created to think -- Interplay of influences -- Discernment requires doubts -- Solving problems with questions -- Sources of doubt -- Locating limits -- Unanswered questions -- Doubts born from pain -- Disillusionment masquerading as doubt -- Resolving doubts -- An authentic journey -- Retracing the path -- Thinking in community -- An incomplete process -- Single-session discussion guide.
Includes bibliographical references.
Print version record.
Keywords: Faith; Faith; RELIGION / Christian Theology / Soteriology; Electronic books